Growth, yield and costs during the first three years of mahogany (Swietenia macrophylla King) established in agroforestry systems - Chinchilla-Mora, Orlando (2020)
Establishing high-value timber species in agroforestry systems (AFS) represents the opportunity for farmers to produce wood with agricultural crops as a primary goal. Mahogany is a widely known species, its wood is precious and easy to work, information on its growth, yield and costs in AFS through real documented cases is extremely rare. The objective of the present investigation was to determine yields and costs of five different AFS. The average diameter reached by the clones at Venecia site was 10.1 cm*tree-1 and 7.3 m*tree-1 in total height at 36 months old (MAI: 3.37 cm*tree-1*year-1 and 2.43 m*tree-1*year-1, respectively). The average yield of the genetic set at Venecia was 0.037 m³*arb-1, values of up to 0.0540 m³*arb-1 were recorded. The combination with cocoa at Sarapiquí at 31 months old recorded an average height and diameter of 7.66 m*tree-1 and 7.55 cm*tree-1, respectively. The sites combined with coffee show that as rise in the altitudinal floor, growth in height, diameter and volume decreases. If we compare Venecia with Santa Lucia, the difference in volume for clone 96 at both sites is 384 % at the age of 3 years old (Santa Lucia 0.0097 m³*tree-1 and Venecia 0.0470 m³*tree-1). The purchase price of the plant constitutes the most important item to consider within all caoba costs. The cost of the forestry component increases per unit area as the number of trees increases and the greater the number of trees you get lower unit cost.